Respuesta agronómica del cultivo de pimiento (Capsicum annuum L.) a la aplicación de fertilizantes nitrogenados. - Cruz Moreira, Ariel Lenin (2020)
The application of nitrogen fertilizers applied to pepper cultivation has been of great interest in the agricultural field, because the applied nitrogen plays an important role in the phenological and productive development, currently different nitrogen-based fertilizers are marketed, where they indicate the Ideal dosages for each crop, however, the effect it could have on yield by applying doses that are not recommended of the product is unknown. For this reason, the present research aimed to evaluate the agronomic response of the pepper crop (Capsicum annuum L.) to the application of three doses of nitrogen fertilizers in the Buena Fe area. A randomized complete block design was used (DBCA) with two factors, being factor A the doses (10% less than the recommended dose, recommended dose, 10% more than the recommended dose) and factor B the fertilizers (urea, active urea, YaraVera Amides). The study consisted of the application of nitrogen fertilizers in three different doses, where they were evaluated; Plant height at 30 days after sowing (dds), plant height at 60 dds, fruit weight, fruit diameter, fruit length, number of fruits per plant, yield (kg / ha-1). The results of the research showed significant differences between the treatments under study, the results obtained for the variable height of the plant where it was fertilized with YaraVera Amides (T9), Urea Active (T6) reached the highest values with averages of 44.20 and 43.70 cm. On the other hand, the yields evaluated between treatments suggest that the plots fertilized with YaraVera Amidas (T9) and Urea Active (T6) presented higher yields, reaching values for T9 of 26481.17 kg / ha-1 and T6 with an average of 24289.67 kg / ha-1, being statistically higher between treatments. Once these results have been obtained, the research suggests considering the treatments T9, T6 within the technological packages of pepper cultivation with the application of nitrogen fertilizers such as YaraVera Amidas (T9) and Urea Active (T6) in dosage 110 kg / ha-1 with The purpose of increasing the yields in kg / ha-1 in the pepper crop. Keywords: fertilizer, nitrogen, yield